Principal Leadership Strategies in Improving Teacher Performance: A Literature Review - Hasibuan, Dina Sari; Hasibuan, Ifdlol Amarullah; Ulfah, Mariam; Siregar, Julmahdi; Harahap, Amin (The Future of Education Journal, 2026)
School principal leadership plays a strategic role in improving teacher performance as one of the key determinants of educational quality in schools. Principals function not only as administrative managers but also as instructional leaders who guide, supervise, and motivate teachers. This study aims to analyze principal leadership strategies in improving teacher performance based on findings from previous studies. The research employed a literature review design by analyzing relevant Indonesian national journal articles published within the last ten years. Data were collected through a systematic search using Google Scholar with keywords related to principal leadership and teacher performance. The data were analyzed using a qualitative descriptive approach through data reduction, thematic categorization, and synthesis of research findings. The results indicate that effective principal leadership strategies in improving teacher performance include academic supervision, enhancement of teacher motivation and discipline, exemplary leadership, participative leadership, effective interpersonal communication, and the strengthening of school culture. These strategies are interconnected and should be implemented in an integrated manner to enhance teacher professionalism and sustainable performance improvement. This study is expected to serve as a reference for school principals and educational stakeholders in developing effective leadership practices in schools.